Can re-infiltration process be ignored for flood inundation mapping and prediction during extreme storms? A case study in Texas Gulf Coast region. (September 2022) - Li, Zhi; Chen, Mengye; Gao, Shang; Wen, Yixin; Gourley, Jonathan J.; Yang, Tiantian; Kolar, Randall; Hong, Yang
Abstract: Coupled Hydrologic & Hydraulic (H&H) models have been widely applied for flood simulations, yet the modern H&H models suffer from one-way and weak coupling and particularly disregarded run-on infiltration, which could compromise the model accuracy. In this study, we assess the H&H model performance with and without re-infiltration process in extreme flooding events. Results highlight that the re-infiltration process should not be disregarded even in extreme flood simulations. Saturated hydraulic conductivity and antecedent soil moisture are found to be the prime contributors to such differences. For the Hurricane Harvey event, the model performance is verified against stream gauges and high water marks, from which the re-infiltration scheme increases the Nash Sutcliffe Efficiency score by 140% on average and reduces maximum depth differences by 17%. Meanwhile, the recent update of the CREST-iMAP model Version 1.1, which incorporates two-way coupling and re-infiltration scheme, is released for public access. Highlights: A coupled hydrologic-hydraulic model takes re-infiltration scheme into account. The advantages of re-infiltration are quantified and discussed for extreme events. We advocate the importance of re-infiltration even in extreme events.